Symbols in the Shrine of Ushi Deity of Akpolu Etche in South-South Nigeria - Amadi, Emmanuel Echezolochi (NIU Journal of Social Sciences, 2025)
This essay focuses on symbols in the shrine of Ushi deity of Akpoku Etche. The paper posits that symbols found in the shrine of Ushi deity are classified into the following groups: Artistic symbolism, symbolism of vegetable materials, symbolism of constructed images and objects, and communicative symbolism. The paper argues that symbols in the shrine of Ushi deity has helped to create a medium for communion and communication among the devotees on one hand, and between them and the object of worship on the other hand. The paper also contends that these symbols are like the hub which connect and link the devotees of Ushi deity to the supersensible world. The methodology adopted was oral interviews (reports of the devotees of Ushi deity and handed down tradition from the custodians of Akpoku custom and tradition) and secondary sources (published materials). The study adopts phenomenological approach to describe and interpret the symbolic interaction between the devotees and the object of worship. The study also adopts “symbolic interactionism” as theoretical frameworks. Finding reveals that through these symbols the devotees enter into a relationship with the supersensible world. Keywords: Akpoku, Ushi deity and Symbols.